Agricultural R&D budgetary support to potential areas in Indian Agriculture - Kumar, Shiv (Indian Farming, 2022)
Budgetary support in emerging areas of agricultural research and development, and enhancing organizational skills of actors engagedin interdisciplinary areas and inter ministries/departments is expected to create an enabling environment for interactions and knowledge sharing among multiple-stakeholders and to create capacity to innovate products, processes and institutions to respond to market opportunities and enhance economic efficiency.